Diagnostic and prognostic biomarkers of common urological cancers based on aberrant DNA methylation. (4th September 2018) - Peng, Ding; Ge, Guangzhe; Xu, Zhengzheng; Ma, Qin; Shi, Yue; Zhou, Yuanyuan; Gong, Yanqing; Xiong, Gengyan; Zhang, Cuijian; He, Shiming; He, Zhisong; Li, Xuesong; et al.
Aim: We intended to construct DNA methylation-based models for the diagnosis and prognosis of three common urological cancers including prostate adenocarcinoma, renal clear cell carcinoma and bladder urothelial carcinoma.Materials & methods: Total 450K methylation array data from the cancer genome atlas and gene expression omnibus datasets were downloaded. Moderated t-statistics and least absolute shrinkage and selection operator method were used to build diagnosis and prognosis models.Results: Our diagnostic panels including 128 CpG sites had high sensitivity and accuracy in distinguishing samples and could identify lymphatic metastases in prostate adenocarcinoma patients. The prognostic models with 19 CpG sites for renal clear cell carcinoma and 21 CpG sites for bladder urothelial carcinoma were able to distinguish high- and low-risk patients and improve the predictive ability of the tumor node metastasis staging system.Conclusion: DNA methylation may afford reliable biomarkers in the diagnosis and prognosis of common urological cancers.